Foreign Ownership and Stock Return Volatility in Vietnam: the Destabilizing Role of Firm Size - To, Anh Tho; Suzuki, Yoshihisa; Vuong, Bao Ngoc; Tran, Quoc Tuan; Do, Khoa (Organizations and Markets in Emerging Economies, 2019)
This study aims to examine the relevance of foreign ownership to stock return volatility in the Vietnam stock market over ten years (2008 - 2017). After applying the fixed effects regressions and the extended instrumental variable regressions with fixed effects, we find that foreign ownership decreases the volatility of stock returns. However, the stabilizing impact of foreign ownership on stock return volatility becomes weaker in large firms since the coeffcient of the interaction term between firm size and foreign ownership turns out to be significantly positive. The estimated results remain robust when we use the future one-year volatility, other than the current one, as an alternative measure of the dependent variable.